ПЕРСПЕКТИВЫ ИСПОЛЬЗОВАНИЯ МИКРОМИЦЕТОВ ДЛЯ БОРЬБЫ С ФИТОПАРАЗИТИЧЕСКИМИ НЕМАТОДАМИ (Experimental biology, 2015)
The fungal strains having nematocide activity and nutrient medium for the cultivation of fungi and enhance their nematocide properties were selected. Identified strains of fungi of the Aspergillus; Penicillium andTrichodermasorts, by the action of which, the mortality of nematodes ranged from 57% to 78%. The complex of biologically active substances studied strains consists of indole substances and alkaline protease.
Keywords: nutrient medium; protease